An observational approach for exploring variability in young children's regulation‐related skills within classroom contexts. Issue 6 (24th February 2022) - McCoy, Dana Charles; Koepp, Andrew E.; Jones, Stephanie M.; Bodrova, Elena; Leong, Deborah J.; Deaver, Abigail Hemenway
Abstract: Prior work has conceptualized children's executive function and self‐regulation skills as relatively stable across short periods of time. Grounded in long‐standing contextual theories of human development, this study introduces a new observational tool for measuring children's regulatory skills across different naturally occurring situations within early childhood classrooms. Using 460 observations of 91 children ( M age = 5.54 years) in 16 socio‐demographically diverse Prekindergarten and Kindergarten classrooms, we found that this tool—the Regulation‐Related Skills Measure (RRSM)—reliably captured observed dimensions of young children's attention control and inhibitory control, but failed to appropriately represent more "internal" regulatory processes (e.g., working memory). Associations between the RRSM and other measures of children's executive function and self‐regulation (i.e., direct assessments, adult reports) were low to moderate ( r = 0.03 to 0.44), suggesting these tools are likely to be complementary in that they provide overlapping but ultimately distinct information regarding children's regulatory performance. Finally, results suggested substantial within‐child variation in regulatory behaviors across different situations within the classroom, with the same children demonstrating consistently stronger attention control and inhibitory control during transitions than during either teacher‐ or student‐directed activities. These findings underscore the situationally‐dependent nature of children's self‐regulatory performance, with implications for both theory and practice. Future research is needed to replicate these findings in more diverse, representative samples of children. Abstract : We developed a new measures for capturing children's attention control and inhibitory control across different everyday situations in early childhood classrooms. Scores from this measure, the Regulation‐Related Skills Measure (RRSM), were only weakly correlated with other measures of self‐regulation and executive function. Children demonstrated stronger RRSM scores during transitions than teacher‐ or student‐directed activities, suggesting that enactment of attention control and inhibitory control is situation‐dependent.